Enriched Milk Drinks for Vitamin Deficiency Correction in Toddlers and Preschoolers - Vera M. Kodentsova ("Paediatrician" Publishers LLC, 2017)
After switching to general diet, children aged over 1 year lack vitamins D, B12, C, as well as folates, calcium, iodine, iron, zinc, and docosahexaenoic acid. High prevalence of multi-micronutrient deficiency among toddlers and preschoolers constitutes grounds for administration of food products rich in micronutrients, including beverages made on different bases (juices, cow's milk, etc.). Baby food products for young children as well as micronutrient-enriched milk drinks have advantages over other dietary dishes because the vitamins and minerals contained in them correspond to the child's age requirement. The article discusses disagreements in the name of milk drinks for children over 1 year. The article also considers conformity of the quality of such drinks with the regulatory framework in force in the Russian Federation. The analysis of scientific literature on the effectiveness of inclusion of micronutrientenriched beverages in the diet of toddlers and preschoolers was carried out. Children whose diet includes only cow's milk with excessive intake of protein and saturated fats have a risk of developing deficiency of alpha-linolenic and docosahexaenoic acids, iron, vitamins C and D. Inclusion of milk drinks in the general diet guarantees adequate consumption of micronutrients, provides the body with vitamins and microelements, reduces disease incidence, improves cognitive functions of children.